A Facile Fabrication of ZnFe2O4/Sepiolite Composite with Excellent Photocatalytic Performance on the Removal of Tetracycline Hydrochloride - Zhang, Caihong; Han, Xiaoyu; Wang, Fei; Wang, Lijuan; Liang, Jinsheng (Frontiers in Chemistry, 2021)
The excellent photo-response of ZnFe2O4 in the visible light region makes it a promising catalyst, whereas some defects like serious particle agglomeration and easy recombination of photo-generated electron-hole pairs hinder its application. In this work, the ZnFe2O4/sepiolite (ZF-Sep) composites were synthesized using a co-precipitation method. The obtained ZF-Sep composites were characterized by XRD, SEM, TEM, FT-IR, XPS, BET, VSM and DRS. Moreover, the photocatalytic performance was evaluated by the tetracycline hydrochloride removal efficiency under simulated visible light illumination. The results displayed that the ZnFe2O4 with average sizes about 20 nm were highly dispersed on sepiolite nanofibers. All the composites exhibited better photocatalytic performance than pure ZnFe2O4 due to the synergistic effect of the improvement on the agglomeration phenomenon of ZnFe2O4 and the reduction on the recombination rate of photo-generated electrons and holes. The optimum removal efficiency was that of the ZF-Sep-11 composite, which reached 93.6% within 3 h. Besides, the composite exhibited an excellent stability and reusability. Therefore, ZF-Sep composite is a promising catalyst for the treatment of wastewater contained antibiotics.